The Contribution of Private Sector in the provision of Higher Education in Tanzania: Growth and Challenges - Mkulu, Demetria Gerold (International Journal of Humanities and Education Development (IJHED), 2020)
This study sought to capture the involvement of the private sector in the provision of higher education: Growth and administrative challenges facing private universities in Tanzania. Data was gleaned through the employment of a questionnaire, an in-depth interview guide, and a document analysis guide; five universities were included in the study. A sample size of 150 participants were involved in the study, including 100 Lecturers, 40 university students and 10 private university managers in the country. The research utilized mixed methods, convergent parallel research methods designs, which involved quantitative and qualitative paradigms. The instruments for data collection were a questionnaire, an interview, and observation. Validity and reliability were checked, the result of Cronbach's alpha was 0.861 indicating that the instruments were valid and reliable. Data was collected, coded using expressive statistics with the support package for Social Sciences (SPSS) Version 21. Qualitative information was coded by the naming of conceptual categories and main themes to obtain numerous realities. The current study established that private universities are contributing greatly to the provision of quality education in Tanzania. These include the fact that private universities outnumber public universities hence they enroll more students, they also employ more lecturers and their students perform better than those in public universities. Nevertheless, they encounter challenges such as lack of funds, research and publication, quality assurance specifically TCU issues which hinders the growth of private universities and loss of qualified experienced academic staff. This study recommends that private universities should endlessly focus at future staffing levels and guarantee strategies are revised so as to involve more students, managers in private universities need to expand, diversify and remodel their way of operations as well as putting in place the necessary support systems and resources as intervention measures to strengthen the provision of higher education to the students enrolled in the universities. There is also a need for universities to conduct more research for social transformation. Universities should partner with industry in the improvement of technology and the generation of market- driven programs.